Bibliometric Review on Digital Economy and Industry Convergence: The Impact of Digitalization on Business Adaptation and Innovation - Judijanto, Loso; Yusniar, Yusniar; Nurrohman, Rosyid; Sudarmanto, Eko; Supriatna, Endang (West Science Interdisciplinary Studies, 2024)
This study presents a bibliometric analysis of research on digital economy and industry convergence, with a focus on the impact of digitalization on business adaptation and innovation. Using data from key databases, including Scopus and Web of Science, and visualized through VOSviewer, the analysis reveals key themes, influential authors, and evolving research trends from 2000 to 2024. The findings highlight that "digitalisation" remains central to the discourse, particularly in relation to manufacturing, automation, and business process digitisation. Recent research shows a growing focus on sustainability and the role of digitalization in addressing environmental challenges. Additionally, the impact of COVID-19 has accelerated the adoption of digital strategies, with businesses increasingly focusing on flexibility, risk management, and business resilience. The analysis of author collaboration networks identifies prominent contributors and interdisciplinary efforts in this field. This study underscores the importance of digital innovation for business growth and calls for further exploration of how digital technologies can enhance sustainability and resilience in a post-pandemic world.